2007
DOI: 10.1093/brain/awm147
|View full text |Cite
|
Sign up to set email alerts
|

Ageing and early-stage Parkinson's disease affect separable neural mechanisms of mesolimbic reward processing

Abstract: The ability to learn stimulus-reward associations on the basis of reward prediction errors critically depends on the mesolimbic dopaminergic system including the dopaminergic midbrain and the ventral striatum. It is known that healthy elderly and patients with Parkinson's disease are less proficient than healthy young adults in learning stimulus-reward contingencies, but it is unclear whether this is due to dysfunctional mesolimbic reward prediction or due to deficiency in processing the rewards per se. We use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

30
172
3

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 181 publications
(205 citation statements)
references
References 52 publications
30
172
3
Order By: Relevance
“…In fact, one might not assume this relationship to be maintained in PD. A recent neuroimaging study in PD patients after withdrawal of medication, elderly and young healthy controls showed that though RPE processing seems relatively preserved, PD patients and elderly controls show a markedly impaired reward prediction signal (Schott et al, 2007). Given the subtle nature of this relationship in young participants, the relative loss of this relationship in elderly and PD van Eimeren et alpatients, and the lack of such a relationship in our study, we assume that a putative influence can only be of negligible quantity.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, one might not assume this relationship to be maintained in PD. A recent neuroimaging study in PD patients after withdrawal of medication, elderly and young healthy controls showed that though RPE processing seems relatively preserved, PD patients and elderly controls show a markedly impaired reward prediction signal (Schott et al, 2007). Given the subtle nature of this relationship in young participants, the relative loss of this relationship in elderly and PD van Eimeren et alpatients, and the lack of such a relationship in our study, we assume that a putative influence can only be of negligible quantity.…”
Section: Discussionmentioning
confidence: 99%
“…To investigate the relationship between the neural response during reward anticipation versus no reward anticipation and the behavioral benefit in the rewarded relative to the neutral condition, we computed the relative reaction time (RT) advantages as [(RT no reward Ϫ RT reward )/RT no reward ] for all subjects, in line with common definitions (Schott et al, 2007). Accordingly, we computed the behavioral benefit from specific oculomotor preparation as [(RT neutral prep Ϫ RT spec prep )/RT neutral prep ].…”
Section: Fmri Acquisition Glm and Functional Connectivitymentioning
confidence: 99%
“…However, some functional neuroimaging studies have examined brain activity in the striatum, a target region for midbrain dopaminergic neurons (Lyndbalta and Haber, 1994). Such studies have found that older adults show robust responses in ventral and/or dorsal striatum to positive outcomes (Schott et al, 2007;Samanez-Larkin et al, 2010). Results from studies examining reward anticipation are more mixed, with older adults showing less ventral striatal activation than younger adults in some cases (Schott et al, 2007; but not in all studies .…”
Section: How Can the Current Findings Be Reconciled With Age-related mentioning
confidence: 99%
“…Such studies have found that older adults show robust responses in ventral and/or dorsal striatum to positive outcomes (Schott et al, 2007;Samanez-Larkin et al, 2010). Results from studies examining reward anticipation are more mixed, with older adults showing less ventral striatal activation than younger adults in some cases (Schott et al, 2007; but not in all studies . There are also age differences in whether stronger responses to outcomes are seen early or late in the learning phase of a probabilistic learning task .…”
Section: How Can the Current Findings Be Reconciled With Age-related mentioning
confidence: 99%